2019
DOI: 10.3390/su11020343
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between CSR and Financial Performance

Abstract: This study analyzed whether a systematic relationship exists between corporate social responsibility (CSR) performance and corporate financial performance using 191 sample firms listed on the Korea Exchange. The Korea Economic Justice Institute (KEJI) index of 2015 was used to measure CSR performance; profitability and firm value were used to measure corporate financial performance. Return on assets was used as a proxy for profitability, and Tobin’s Q was used as a proxy for firm value. The correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
227
3
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(337 citation statements)
references
References 82 publications
(78 reference statements)
19
227
3
12
Order By: Relevance
“…The results imply that as CSR activities increase, long-term performance decreases. However, when we introduce an interaction term, CSR × OC, which combines the CSR dummy (if CSR > 0, then CSR_D = 1, otherwise 0) with OC ranks (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as in models 3 and 4, the results are totally different. The relationship between CSR and AAR turns to positive and significant (p-value < 5%) in model 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results imply that as CSR activities increase, long-term performance decreases. However, when we introduce an interaction term, CSR × OC, which combines the CSR dummy (if CSR > 0, then CSR_D = 1, otherwise 0) with OC ranks (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as in models 3 and 4, the results are totally different. The relationship between CSR and AAR turns to positive and significant (p-value < 5%) in model 3.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies on CSR have covered the relationship between CSR and financial performance. A number of empirical studies have shown that the more CSR activities a company is involved in, the better its long-term performance (e.g., [8,9]). Li et al [10] investigated equity returns and showed that a portfolio consisting of the best CSR companies in the world generated positive abnormal returns.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature reveals findings concerning the consequences of responsible practices in business performance. The bibliometric study carried out by Van Beurden and Gössling (2008) provides clear empirical evidence of a positive correlation between firms' social and financial performance (Griffin, 2000;Margolis & Walsh, 2001;Orlitzky, Schmidt, & Rynes, 2003;Maron, 2006;Wu, 2006;Cho, Chung, & Young, 2019). Other authors, however, point to negative correlations (Griffin & Mahon, 1997), causal ambiguity (Waddock & Graves, 1997a, 1997b, or to a bidirectional relation (Choi, Kwak, & Choe, 2010).…”
Section: Literature Review and Formulation Of The Modelmentioning
confidence: 99%
“…We measure profitability and firm value using Return on Assets (ROA) and Tobin's Q as the respective proxies. In particular, ROA is calculated dividing the firm's net income by its total assets and measures how efficiently firm assets are employed to generate financial profit (Cho et al, 2019). Tobin's Q, instead, is calculated dividing the firm's market value of total assets by their cost of replacement.…”
Section: Dependent Variablesmentioning
confidence: 99%